ANALISIS KAUSALITAS OUTPUT, KURS, SUKU BUNGA DAN INFLASI DENGAN INVESTASI ASING DI INDONESIA - Maltio Maltio; Melti Roza Adry; Yeniwati Yeniwati (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2015)
This study investigates the relationship among output, exchange rate, interest rate (BI rate) and inflation with foreign investment (FDI), in Indonesia. The relationship among that variables is very important, because Indonesia getting start to optimize the growth economic arising out of crisis.This study used a VAR model to see causality output, exchange rate, interest rate (BI rate) and inflation with foreign investment (FDI). The data used is the time series data from 2003: 1-2014: 3 collected through documentation of relevant government agencies. In more detail, the technique used is the Vector Autoregression (VAR) to analyze the causal relationship.The results obtained indicate that foreign direct investment (FDI) has a causal relationship with the output. But there was no causal relationship between foreign direct investment (FDI) with the exchange rate, interest rate (BI rate) and inflation only unidirectional relationship in which foreign investment (FDI) effect on the exchange rate and foreign investment affect the BI rate.Keyword : foreign investment, exchange rates, interest rate ad inflation